2021
DOI: 10.1039/d1ta01639c
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometrically driven disorder and local diffusion in NMC cathodes

Abstract: Major structural differences in lithium nickel manganese cobalt oxides (NMC) prepared under identical conditions have been uncovered using neutron powder diffraction. Sample NMC-622 was obtained as a single R3 ̅m...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…At OCV, with close to full Li occupancy in the cathode, D Li is at its lowest due to the difficulty of Li + ion diffusion to a vacant site (Figure c). The value of D Li found before cycling of ∼3.4 × 10 –11 cm 2 s –1 compares well to that found by a previous μSR study of NMC811 (reported as 2.9 × 10 –11 cm 2 s –1 ) …”
Section: Resultssupporting
confidence: 90%
“…At OCV, with close to full Li occupancy in the cathode, D Li is at its lowest due to the difficulty of Li + ion diffusion to a vacant site (Figure c). The value of D Li found before cycling of ∼3.4 × 10 –11 cm 2 s –1 compares well to that found by a previous μSR study of NMC811 (reported as 2.9 × 10 –11 cm 2 s –1 ) …”
Section: Resultssupporting
confidence: 90%
“…Note that for LCO, velocities cannot be extracted during lithiation as it is beyond our time resolution (100 s). These values sit at the lower end of those reported previously in the literature (1 nm s -1 to 50 nm s -1 ) 24,[59][60][61][62][63][64] . However, in this work, the transport velocities reported are through individual polycrystalline particles i.e.…”
Section: Surface-to-core Transportsupporting
confidence: 50%
“…Above this temperature, a brief period of increasing 003 R /104 R was observed, but was followed by a subsequent decrease, indicating a return to a more disordered state. At no point did the 003 R /104 R ratio approach the typical value of 1.3 reported for completely site‐ordered LiNi 0.8 Mn 0.1 Co 0.1 O 2 [ 31 ] and observed by ex situ XRD (Figure S1a, Supporting Information) for powders held at 750 °C for 10 h. This low 003 R /104 R indicates a certain amount of disorder (i.e., Ni in the Li layer), and is partially due to the absence of the typical extended hold at the final calcination temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Co and Mn were only included in the 3b positions. [9,31] Domain sizes were modeled using Lorentzian peak broadening not accounted for by instrumental broadening. Example comparisons of calculated and observed diffraction patterns are shown in Figure S11, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation